The role and importance of national wrestling in the system of physical education - Arabov Arif Alisherovich; Amirov Anvar Saidmurod oglu (Genius Journals, 2022)
The article provides some recommendations on the importance of using modern pedagogical technologies in the field of wrestling, worldview and thinking, the formation of scale, the formation of physical, spiritual and moral qualities of the Department of Preschool Education and Pedagogy
Keywords: National Wrestling; Bukhara; Fergana; Olympic